HYDRODYNAMIC CHARACTERISTICS OF ELITE SWIMMERS OF DIFFERENT GENDERS AT FINAL PERIOD OF TRAINING FOR MAJOR COMPETITIONS - Kolmogorov, S.V.; Rumyantseva, O.A.; Vorontsov, A.P.; Gudkov, A.B. (Theory and Practice of Physical Culture, 2022)
Hydrodynamic characteristics of elite female and male swimmers were determined by the four variants of the perturbation method at the phase of decrease in training load before the 2016 Olympic Games in Rio de Janeiro and the 2017 World Championship in Budapest. Further, the ten best swimmers of both genders were selected by their maximal swimming velocity (v0max) in all athletic strokes (80 subjects altogether). As a result of the proper processing of the data, statistical models of quantitative values of active drag force (Fr(ad), the dimensionless hydrodynamic coefficient (Cx(ad)) and total external mechanical power (Pto) were determined. In all four strokes, due to their essential superiority in Pto, men have higher magnitudes of v0max than women. Naturally enough that at higher v0max elite male athletes have greater Fr(ad), too. Again, in terms of Cx(ad), there was no statistical difference between women and men within each of the strokes. Consequently, regardless of their gender, elite swimmers may be stated to be equally successful in mastering proficient swimming techniques of all athletic strokes. Besides having an independent scientific significance, the statistical models of Fr(ad), Cx(ad) and Pto allow to increase considerably the quality of the individual analysis of these indicators on athletes of different performance levels. The key criterion for such analysis at the phase of decrease in training load is Cx(ad), which determines the hydrodynamic efficiency of the individual swimming technique in any of athletic strokes in terms of quantity. Keywords: swimming velocity, active hydrodynamic resistance (active drag), mechanical power.